Perceptions of neighbourhood safety and policy response: a qualitative approach - Lub, Vasco (European journal on criminal policy and research, 2017)
Safety perceptions of residents are often analysed through surveys and compared with factual crime developments. Using the Dutch city of Rotterdam as an urban context of improved crime levels, this article provides a critique on standardised surveys in the research of safety perceptions and its presupposed connection to factual crime. Contrasting survey results from the Rotterdam Safety Index with qualitative data from 64 in-depth interviews in four districts, the qualitative narrative contradicts findings from the survey and implies more nuanced and diversified policy responses to safety issues. Because of the tendency of surveys to connect safety perceptions to factual crime, their unsuitability to catch subtle perceptions and their inability to expose new viewpoints, we argue for de-quantification: a lesser dependency on—but not a repeal of—survey data in this area, supplemented by a periodic qualitative approach in the research of crime and safety information (qualitative monitoring).